1992
DOI: 10.1161/01.atv.12.8.945
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is a potential confounder of the Chlamydia pneumoniae-coronary artery disease association.

Abstract: Two recent studies, which did not adequately control for smoking status, found associations between Chlamydia pneumoniae serological titers and various manifestations of coronary artery disease (CAD). The validity of C. pneumoniae-CAD associations found in case-control studies has been criticized on the basis that smoking, known to be associated with CAD and hypothesized to be associated with C. pneumoniae seroreactivity via an increased prevalence of respiratory infection in smokers, could be an uncontrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
4
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 6 publications
(5 reference statements)
5
43
4
2
Order By: Relevance
“…[23][24][25] In this study, we found no noteworthy interactions (ie, effect modification) by these factors with the association between C. pneumoniae and hypertension. Subjects in the HT and control groups also differed in some other demographic characteristics whose influences on the risk of C. pneumoniae infection were unknown (Table).…”
Section: Pneumoniae and Hypertensioncontrasting
confidence: 52%
“…[23][24][25] In this study, we found no noteworthy interactions (ie, effect modification) by these factors with the association between C. pneumoniae and hypertension. Subjects in the HT and control groups also differed in some other demographic characteristics whose influences on the risk of C. pneumoniae infection were unknown (Table).…”
Section: Pneumoniae and Hypertensioncontrasting
confidence: 52%
“…Current [19,20] and exsmokers [20] have more seropositivity and higher titres of C. pneumoniae antibodies than non-smokers. It has been suggested that the associations between smoking and chronic cardiopulmonary disease may be mediated by the promotion of C. pneumoniae infection [19]. This small study was not designed to address pathogenic pathways involving smoking, infection and asthma, nor was it powerful enough to detect potentially significant interactions of smoking and infection.…”
Section: Resultsmentioning
confidence: 95%
“…We found that chlamydial antibodies were significantly more common among men and smokers, validating associations noted by others. 23,24 We specifically sought an interaction between C pneumoniae, smoking, and CV events, hypothesizing synergy between smoking and infection. Although the interaction term was statistically significant, the relation between C pneumoniae IgA and CV events persisted only in former smokers or never-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, smoking may be a confounding factor in the C pneumoniae-heart disease association, as originally suggested by Hahn and Golubjatnikov. 23 Alternatively, smoking and chlamydial infection may be part of the same causal pathway, such that no excess risk is associated with chlamydial infection after controlling for smoking.…”
Section: Discussionmentioning
confidence: 99%